Etude ethnobotanique des ressources forestières ligneuses de la forêt marécageuse d'Agonvè et terroirs connexes au Bénin - Tenté, AHB.; Lougbégnon, OT.; Houessou, GL.; Dossou, ME.; Codjia, JTC. (Tropicultura, 2012)
Ethnobotanical Study of Ligneous Species in Agonvè Swampy Forest and Surrounding Area in Benin. Quantitative ethnobotanical study was conducted with the local community around Agonve forest, which is one of southern Benin swampy forest. This study enables to describe the different use categories of woody plant species for local population and to determine the use value (UV) of each species. A total of 28 woody species were identified as useful species for the local population in different use categories such as medicine, food, fire wood and construction. The principal component analysis on the matrix (use forms* species) showed that the populations did not log the tree species which they considered as useful for food or medicine. There was no significant difference regarding the overall ethnobotanical use value between the surrounding villages (p= 0.344, F= 1.08 and dF= 2). Among the useful species, Dialium guineense (UVT= 8.98), Spondianthus preussii (UVT= 7.68) and Raphia hookeri (UVT= 7.16) were the most use species by the local population. Finally the study pointed out the importance of the ethnobotanical use value as tool to select the species which conservation must be emphasized in the management plans to meet not only the need of the populations but also to improve the conservation statute of the species.